Management of Aplastic Anemia in Pregnancy: A Case Report: Manajemen Anemia Aplastic Pada Kehamilan: Laporan Kasus - Suskhan Djusad; Yoarva Malano (Indonesian Socety of Obstetrics and Gynecology, 2020)
Aplastic anemia was first recognized by Ehrlich in 1888, although the pathogenesis of aplastic anemia has remained elusive. Aplastic anemia is a subtype of anemia characterized by pancytopenia and a hypocellular bone marrow which are the risk factor can be due to chemicals, drugs, infections, irradiation, leukemia, and inherited disorders. There is universal agreement that pregnancy complicated by aplastic anemia is a serious condition. The risk to the mother is mainly in the form of hemorrhage meanwhile the fetus may suffer from growth restriction and even intrauterine death. Most of the fetal complications are due to maternal anemia. We here present one cases of pregnancy complicated by aplastic anemia, which were seen within 3 months at our hospital. This high incidence is because the hospital is a top national care referral unit with good hematology and blood bank support. Keyword: aplastic anemia, pregnancy, pancytopenia Abstrak Anemia aplastik pertama kali dikenali oleh Ehrlich pada tahun 1888, walaupun patogenesis anemia aplastik masih sulit dipahami. Anemia aplastik adalah subtipe anemia yang ditandai dengan pansitopenia dan hiposeluler sumsum tulang yang merupakan faktor risiko yang dapat disebabkan oleh bahan kimia, obat-obatan, infeksi, iradiasi, leukemia, dan kelainan bawaan. Terdapat kesepakatan universal bahwa komplikasi kehamilan berupa anemia aplastik merupakan kondisi serius. Risiko kepada ibu hamil terutama dalam bentuk perdarahan sementara janin dapat mengalami hambatan dalam pertumbuhan dan bahkan kematian dalam kandungan. Sebagian besar komplikasi janin disebabkan oleh anemia pada maternal. Kami di sini menyajikan satu kasus komplikasi kehamilan berupa anemia aplastik, yang ditemukan dalam waktu 3 bulan di rumah sakit kami. Kejadian yang tinggi ini karena rumah sakit adalah unit rujukan perawatan nasional teratas dengan hematologi yang baik dan dukungan bank darah.